The variation of homogentisate gerenylgeranyl transferase (HGGT) promoter sequence in different Elaeis guineensis genotypes - Ismail, Khairul Anwar (2013)
Vitamin E can be divided into two important forms which are tocotreinols and tocopherols. Elaeis guineensis revealed high content of tocotreinols compared to tocopherols. Homogentisate gernylgeranyl transferase (HGGT) is involved in the biosynthesis of tocotrienols. It has an important role as it catalyzes the first committed step in tocotrienol synthesis. The vitamin E content of the Tanzanian population in the Elaeis guineensis germplasm collection at MPOB shows a high degree of variability (ranging from 300 – 3200 ppm). Some of the palms have high vitamin E content while others have very low vitamin E lower than the commercial palms which contains around 700 ppm of vitamin E. The aim of the study was to detect sequence variation in the forms of single nucleotide polymorphism (SNP) by comparing individuals from the Tanzanian population that exhibited low and high vitamin E content. The project involves analyzing the promoter sequence and detecting for variation that falls within important promoter motifs. Through out the study, there 91 SNPs were detected between HGGT promoter sequence of Tanzanian plams with low and high vitamin E content. The 91 detected SNPs, there were only 9 SNPs that fall within important promoter motif.